2016
DOI: 10.12968/bjhc.2016.22.11.544
|View full text |Cite
|
Sign up to set email alerts
|

Defining goal terms in development and health

Abstract: Goal, aim, objective and target are conceptually different. New frameworks for writing complete goal statements are proposed, including I.T. and O.I.T.T. frameworks for aim and objective respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(20 citation statements)
references
References 9 publications
0
20
0
Order By: Relevance
“…Generically, goal-setting researchers define a goal as the desired end-result of an action that is expected to be achieved at some specified time in the future, and that for which all effort and essential resources are therefore committed to accomplish (Lee et al 1989;Stretcher et al 1995;Fitsimmons 2008;Day and Tosey 2011;Nanji et al 2013). In this article, and in line with a recent review by Ogbeiwi (2016), the term 'objective' refers to a sub-goal, one which expresses a desired outcome: a short-term effect or change expected to result from the outputs of activities performed (OECD 2002). In the hierarchy of goals illustrated in Figure 1, the effects of the immediate output of an intervention lead to the attainment on a short-term of the objective, which in turn on a longer-term contributes to the achievement of the broad or overall aim, which some organisations describe as general goal and development or a higher order objective (OECD 2002).…”
Section: Background On Goals and Objectivesmentioning
confidence: 97%
See 1 more Smart Citation
“…Generically, goal-setting researchers define a goal as the desired end-result of an action that is expected to be achieved at some specified time in the future, and that for which all effort and essential resources are therefore committed to accomplish (Lee et al 1989;Stretcher et al 1995;Fitsimmons 2008;Day and Tosey 2011;Nanji et al 2013). In this article, and in line with a recent review by Ogbeiwi (2016), the term 'objective' refers to a sub-goal, one which expresses a desired outcome: a short-term effect or change expected to result from the outputs of activities performed (OECD 2002). In the hierarchy of goals illustrated in Figure 1, the effects of the immediate output of an intervention lead to the attainment on a short-term of the objective, which in turn on a longer-term contributes to the achievement of the broad or overall aim, which some organisations describe as general goal and development or a higher order objective (OECD 2002).…”
Section: Background On Goals and Objectivesmentioning
confidence: 97%
“…Besides the levels, Figure 1 also differentiates outputs, objectives and aims according to the differing time frames for their attainment and goal attributes. Literature evidences suggest that it may take between three to twelve months to achieve a short-term outcome relating to an objective, and at least five years to accomplish a long-term impact relating at an aim (Ogbeiwi 2016). The synthetic review by Ogbeiwi (2016) reported seven thematic characteristics that distinguish an objective from the other goal types, including its stated object of outcome, specific scope, mid-level or intermediate hierarchy, shortterm time-frame, quantifiable measurability, significance of effectiveness, and expression as a S.M.A.R.T.…”
Section: Background On Goals and Objectivesmentioning
confidence: 99%
“…However, there seems to be controversy over which attributes of the SMART acronym appropriately define a good goal in today's work contexts. The summary of the basic components in Doran's criteria according to literature is: SMART goal statements or objectives must have four basic components, to be specific, measurable, attainable or realistic, relevant and time bound (Ogbeiwi 2016(Ogbeiwi , 2017.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, in development and health sectors, while goals generally express the expected results or desired effects of a planned action or work, they can differ in type, meaning and formulation, depending on the level of organisational or programme framework at which they are set (Ogbeiwi, 2016). Accordingly, the use of the term 'goal' in development organisations means a higher-order objective, and has the same meaning as 'aim' or a long-term goal in a healthcare context.…”
Section: Terminological Definitions Of a Goalmentioning
confidence: 99%
See 1 more Smart Citation